Intraoperative Evaluation of Left Ventricular Diastolic Function by Myocardial Strain in Surgical Aortic Valve Replacement - Foit, André; Brand, Lukas; Mehler, Oliver; Rahmanian, Parwis; Wahlers, Thorsten; Böttiger, Bernd W.; Wetsch, Wolfgang A.; Kammerer, Tobias; Mathes, Alexander; Labus, Jakob (Journal of cardiothoracic and vascular anesthesia, 2024)
Left ventricular (LV) diastolic function predicts patient outcome in cardiac surgery. However, the intraoperative assessment of LV diastolic dysfunction (LVDD) poses challenges due to the load-dependency of most conventional echocardiographic parameters and the dynamic changes of loading conditions in the perioperative course of cardiac surgery. Moreover, LV diastolic function often changes because of the performed procedures and the required supportive interventions. Diastolic strain-based measurements assessed by intraoperative transesophageal echocardiography (TEE) showed to be less load-dependent, and to have strong correlation with LV relaxation, compliance and filling in coronary artery bypass grafting, but there are no reports about evaluation in aortic valve replacement (AVR) surgery. Therefore, we aimed to describe the changes of LV diastolic function assessed by myocardial strain as well as by conventional echocardiographic measurements and common grading algorithms in this patient population. Thirty adult patients scheduled for isolated surgical AVR were included into this prospective observational study. All included patients had preoperative preserved left and right ventricular function, without significant other heart valve disease, and an uneventful intraoperative course. TEE was performed intraoperatively after induction of anesthesia (T1), after termination of cardiopulmonary bypass (T2), and after sternal closure (T3) using General Electric Vivid E95 echocardiography machines and 6VT-D TEE probes. All measurements were performed in stable hemodynamics, in sinus rhythm or atrial pacing, and without significant vasoactive support. EchoPAC v204 software (GE Vingmed Ultrasound AS, Norway) was used for analysis of strain-based measurements of peak longitudinal strain rate during isovolumetric relaxation (SR-IVR), and during early (SR-E) and late (SR-A) LV filling. Assessment of conventional echocardiographic parameters enclosed trans-mitral doppler measures of early (E) and late (A) LV filling, as well as of lateral tissue doppler velocity assessed during early (e´) and late (a´) LV filling. LVDD was graded according to current recommendations and additionally by a strain-based approach. Diastolic strain analysis and grading of LV diastolic function via myocardial strain were feasible in 27 (90%) patients at all timepoints of assessment. LV diastolic function improved significantly after AVR as measured by SR-IVR (T1 v T3, 0.31 s-1 (IQR 0.22; 0.38) v 0.4 s-1 (IQR 0.33; 0.43); p=0.01), SR-E (T1 v T3, 1.13 s-1 (IQR 0.89;1.28) v 1.35 s-1 (IQR 1.10;1.52); p=0.035), and E/SR-IVR (T1 v T3, 2.2m (IQR 1.7;2.8) v 1.6m (IQR 1.3;2.2); p=0.013). Moreover, there was a significant reduction of patients with LVDD grad 2 and 3 as measured by the strain-based algorithm (T1 v T3, n=14 v n= 6; p=0.026). In contrast, conventional echocardiographic measurements and grading algorithms were not able to detect these changes in the same period. In conclusion, evaluation of intraoperative diastolic strain-based measurements and strain-based LVDD grading were feasible in our group of selected AVR patients. LV diastolic function improved after AVR as measured by myocardial strain, however, was not detected by conventional echocardiographic parameters and grading algorithms. Therefore, diastolic myocardial strain might be more sensitive in detecting LVDD by TEE in the perioperative setting with its dynamic changes of loading conditions.